Inner jumping numbers of non-degenerate polynomials - González Villa, Manuel (Mathematische Zeitschrift, 2013)
The inner jumping numbers were introduced by Budur to relate two different measures of the complexity of the singularities of an effective divisor D on a nonsingular complex variety X: the jumping numbers of a pair (X,D) and the Hodge spectrum at a singular point of D. We give an elementary proof for an effective and combinatorial description of inner jumping numbers (<1) of non-degenerate polynomials.
Published online: 18 December 2012
Gesehen am 28.02.2022